A village doctor-led multifaceted intervention for blood pressure control in rural China: an open, cluster randomised trial. Issue 10339 (21st May 2022) - Sun, Yingxian; Mu, Jianjun; Wang, Dao Wen; Ouyang, Nanxiang; Xing, Liying; Guo, Xiaofan; Zhao, Chunxia; Ren, Guocheng; Ye, Ning; Zhou, Ying; Wang, Jun; Li, Zhao; et al.
Summary: Background: The prevalence of uncontrolled hypertension is high and increasing in low-income and middle-income countries. We tested the effectiveness of a multifaceted intervention for blood pressure control in rural China led by village doctors (community health workers on the front line of primary health care). Methods: In this open, cluster randomised trial (China Rural Hypertension Control Project), 326 villages that had a regular village doctor and participated in the China New Rural Cooperative Medical Scheme were randomly assigned (1:1) to either village doctor-led multifaceted intervention or enhanced usual care (control), with stratification by provinces, counties, and townships. We recruited individuals aged 40 years or older with an untreated blood pressure of 140/90 mm Hg or higher (≥130/80 mm Hg among those with a history of cardiovascular disease, diabetes, or chronic kidney disease) or a treated blood pressure of 130/80 mm Hg or higher. In the intervention group, trained village doctors initiated and titrated antihypertensive medications according to a standard protocol with supervision from primary care physicians. Village doctors also conducted health coaching on home blood pressure monitoring, lifestyle changes, and medication adherence. The primary outcome (reported here) was the proportion of patients with a blood pressure of less than 130/80 mm Hg at 18 months. The analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, NCT03527719, and is ongoing. Findings: Between May 8 and November 28, 2018, we enrolled 33 995 individuals from 163 intervention and 163 control villages. At 18 months, 8865 (57·0%) of 15 414 patients in the intervention group and 2895 (19·9%) of 14 500 patients in the control group had a blood pressure of less than 130/80 mm Hg, with a group difference of 37·0% (95% CI 34·9 to 39·1%; p<0·0001). Mean systolic blood pressure decreased by −26·3 mm Hg (95% CI −27·1 to −25·4) from baseline to 18 months in the intervention group and by −11·8 mm Hg (−12·6 to −11·0) in the control group, with a group difference of −14·5 mm Hg (95% CI −15·7 to −13·3 mm Hg; p<0·0001). Mean diastolic blood pressure decreased by −14·6 mm Hg (−15·1 to −14·2) from baseline to 18 months in the intervention group and by −7·5 mm Hg (−7·9 to −7·2) in the control group, with a group difference of −7·1 mm Hg (−7·7 to −6·5 mm Hg; p<0·0001). No treatment-related serious adverse events were reported in either group. Interpretation: Compared with enhanced usual care, village doctor-led intervention resulted in statistically significant improvements in blood pressure control among rural residents in China. This feasible, effective, and sustainable implementation strategy could be scaled up in rural China and other low-income and middle-income countries for hypertension control. Funding: Ministry of Science and Technology of China.